Determinants of Kilang Bateri shoppers’ behaviours - Mahbob, Rinie Sofia (2017)
Shopping behaviours is the study of how individual customers, groups or organizations select, buy, use and dispose ideas, goods and services to satisfy their needs and wants. Therefore, the shoppers’ behaviours assumes that the customers are actors in the marketplace. The perspective of role theory assumes that consumers play various roles in the marketplace. Starting from the information provider, from the user to the payer and to the disposer, customers play these roles in the decisions process. It refers to the actions of the consumers in marketplace and the underlying motives for those actions. This research is determinants of Kilang Bateri shoppers’ behavours. It is also to indicate the relationship between the dependent variable, which is shoppers’ behaviours, and the independent variable, which are aesthetic dimension, exploration dimension and convenience dimension. This research is a quantitative research and the data use for the study collected using distribution of questionnaires. A total of 190 customers of Kilang Bateri took part in answering the questionnaires. The data obtained from the questionnaires were analyzed by using the SPSS software. As a summary, after analyzing the data collected, the result showed that shoppers’ behaviours is significantly relationship with aesthetic dimension, exploration dimension and convenience dimension. This research focuses on possibilities of knowing the determinants of Kilang Bateri shoppers’ behaviours.